The Comparative African Regional Economics of Globalization in Financial Allocation Efficiency - Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2015)
The study assesses the role of globalization-fuelled regionalization policies on financial allocation efficiency in four economic and monetary regions in Africa for the period 1980 to 2008. Banking system and financial system efficiencies are used as dependent variables whereas seven bundled and unbundled globalization variables are employed as independent indicators. The bundling exercise is achieved by means of principal component analysis while the empirical evidence is based on interactive Fixed Effects regressions. The following findings are established. First, financial allocation efficiency is more sensitive to financial openness compared to trade openness and most sensitive to globalization. The relationship between allocation efficiency and globalization-fuelled regionalization policies is: (i) Kuznets or inverted U-shape in the UEMOA and CEMAC zones (evidence of decreasing returns to allocation efficiency from globalization-fuelled regionalization) and (ii) U-shape overwhelmingly in the COMESA and scantily in the EAC (increasing returns to allocation efficiency from globalization-fuelled regionalization). Established shapes are relevant to specific globalization dynamics within regions. `Economic and monetary' regions are more prone to surplus liquidity than purely economic regions. Policy implications and measures of fighting surplus liquidity are discussed.
Keywords: A10; D60; E40; O10; P50; 330; Globalization; Financial Development; Regional Integration; Panel; Africa